2022
DOI: 10.1093/noajnl/vdac093
|View full text |Cite
|
Sign up to set email alerts
|

Identifying clinically applicable machine learning algorithms for glioma segmentation: recent advances and discoveries

Abstract: Background While there are innumerable Machine learning (ML) research algorithms used for segmentation of gliomas, there is yet to be a US FDA cleared product. The aim of this study is to explore the systemic limitations of research algorithms that have prevented translation from concept to product by a review of the current research literature. Methods We performed a systematic literature review on four databases. Of 11,727 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Multiple works demonstrated high accuracy with use of ML for tumor segmentation, identification of images with brain tumors from other pathologies, glioma grade and molecular subtype prediction, differentiation of gliomas from lymphoma or brain metastases. These results suggest that clinical implementation of these algorithms is imminent and will be seen in the clinical practice in the next few years (Subramanian et al, 2021;Afridi et al, 2022;Avery et al, 2022;Bahar et al, 2022;Cassinelli Petersen et al, 2022;Jekel et al, 2022;Tillmanns et al, 2022). The next frontier in neuro-oncology imaging is identification of clinical applications of ML algorithms in clinical practice and determining the aspects of clinical care that can be improved with predictions that can be generated by these algorithms.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple works demonstrated high accuracy with use of ML for tumor segmentation, identification of images with brain tumors from other pathologies, glioma grade and molecular subtype prediction, differentiation of gliomas from lymphoma or brain metastases. These results suggest that clinical implementation of these algorithms is imminent and will be seen in the clinical practice in the next few years (Subramanian et al, 2021;Afridi et al, 2022;Avery et al, 2022;Bahar et al, 2022;Cassinelli Petersen et al, 2022;Jekel et al, 2022;Tillmanns et al, 2022). The next frontier in neuro-oncology imaging is identification of clinical applications of ML algorithms in clinical practice and determining the aspects of clinical care that can be improved with predictions that can be generated by these algorithms.…”
Section: Discussionmentioning
confidence: 98%
“…While there have been several efforts to segment brain lesions from MRIs, such as through the Brain Tumor Segmentation Challenge (BraTS), those efforts have focused on pre-surgical brain MRIs, and have yet to make a substantial translation into clinically useful tools [6][7][8][9]. There have been minimal efforts to develop segmentation algorithms to assist RT planning after surgery.…”
Section: Related Workmentioning
confidence: 99%
“… 36–38 Deep convolutional neural network models have been widely used for tumor segmentation. 39 U-Net architecture and its variants are among the most commonly used models for tumor segmentation. 40 In fact, conventional machine learning (ML) and DL U-Net models proposed for glioma segmentation have been systematically reviewed.…”
Section: Radiomics As a Clinical Toolmentioning
confidence: 99%
“… 40 In fact, conventional machine learning (ML) and DL U-Net models proposed for glioma segmentation have been systematically reviewed. 39 They reported that deep learning models such as U-Net have the potential for deployment in a clinical setting.…”
Section: Radiomics As a Clinical Toolmentioning
confidence: 99%